1999
DOI: 10.1007/s004250050536
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress occurs during soybean nodule senescence

Abstract: Several markers of oxidative stress were measured in 2-to 10-week-old soybean (Glycine max [L.] Merr.) nodules. There were increases in peroxides, protein carbonyls and modi®ed DNA base concentrations with nodule age. The catalytic iron content also increased signi®cantly during nodule ageing. Iron contained in the peribacteroid space was eective in promoting lipid peroxidation and this might contribute to the degradation of the peribacteroid membrane in senescing nodules. The concentration of the oxidized for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
74
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 40 publications
3
74
0
Order By: Relevance
“…7) requires the generation of highly oxidizing ROS, such as the hydroxyl radical, which in turn depend on trace amounts of metal ions (Stadtman, 1992;Halliwell and Gutteridge, 1999). Indeed, catalytic iron (Gogorcena et al, 1995;Evans et al, 1999) and hydroxyl radical production (Becana and Klucas, 1992) have been found to increase in senescing nodules.…”
Section: Discussionmentioning
confidence: 99%
“…7) requires the generation of highly oxidizing ROS, such as the hydroxyl radical, which in turn depend on trace amounts of metal ions (Stadtman, 1992;Halliwell and Gutteridge, 1999). Indeed, catalytic iron (Gogorcena et al, 1995;Evans et al, 1999) and hydroxyl radical production (Becana and Klucas, 1992) have been found to increase in senescing nodules.…”
Section: Discussionmentioning
confidence: 99%
“…To demonstrate such effects experimentally will be difficult, even more so as we did not notice a phenotypic difference between the WT and the C183A-FixK 2 mutant in terms of nodule formation and nitrogen fixation activity. (ii) Although mature nodules are thought to be relatively well protected from ROS by enzymes from both symbiotic partners (37), senescent nodules enhance ROS production and concurrently decrease the antioxidant defense (38,39), leading to oxidative damage of lipids, proteins, and DNA (40). Again, ROS-dependent shut-down of FixK 2 activity would assist in down-regulating symbiotic functions that become futile during senescence.…”
Section: Two Modes Of Fixk2mentioning
confidence: 99%
“…Hydrogen peroxide can be generated via the reduction of oxygen by photosystem I (PS I) and from the Rubisco oxyganase reaction together with the photorespiratory pathway (3).Typically, hydrogen peroxide is one of the primarily ROS production during the soybean nodule senescence. This ROS is severely cytotoxic in that it can cause oxidative damage to membrane-bound proteins, and promote lipid peroxidation and hydroxyl radical generation (12).…”
Section: Biological Nitrogen Fixation and Bradyrhizobium Japonicummentioning
confidence: 99%